Pretreatment of macroalgae for volatile fatty acid production - Thi Nhan Pham; Um, Youngsoon; Yoon, Hyon Hee (Elsevier BV, 2013)
In this study, a novel method was proposed for the biological pretreatment of macroalgae (Laminaria japonica, Pachymeniopsis elliptica, and Enteromorpha crinita) for production of volatile fatty acid (VFA) by anaerobic fermentation. The amount of VFA produced from 40 g/L of L. japonica increased from 8.3 g/L (control) to 15.6 g/L when it was biologically pretreated with Vibrio harveyi. The biological treatment of L. japonica with Vibrio spp. was most effective likely due to the alginate lyase activity of Vibrio spp. However, a considerable effect was also observed after biological pretreatment of P. elliptica and E. crinita, which are red and green algae, respectively. Alkaline pretreatment of 40 g/L of L. japonica with 0.5 N NaOH resulted in an increase of VFA production to 12.2 g/L. These results indicate that VFA production from macroalgae can be significantly enhanced using the proposed biological pretreatments. (C) 2013 Elsevier Ltd. All rights reserved.